2012
DOI: 10.1021/jf300221g
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antitumor Effects of 4,7-Dimethoxy-5-methyl-1,3-benzodioxole Isolated from the Fruiting Body of Antrodia camphorata through Activation of the p53-Mediated p27/Kip1 Signaling Pathway

Abstract: In this study, 4,7-dimethoxy-5-methyl-1,3-benzodioxole (SY-1) was isolated from three different sources of dried Antrodia camphorata (AC) fruiting bodies. AC is a medicinal mushroom that grows on the inner heartwood wall of Cinnamomum kanehirai Hay (Lauraceae), which is an endemic species that is used in Chinese medicine for its antitumor properties. We demonstrated that SY-1 [given as a 1-30 mg/kg body weight intraperitoneal (ip) injection three times per week] profoundly decreased the growth of COLO-205 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In both Hep3B and HepJ5 cells, TCEE treatment induced the expression of cell cycle inhibitors, P21 and P27. Similar P21 induction by TCEE was observed in human melanoma and osteosarcoma cells [ 16 ], whereas the P27 induction by TCEE was observed in human colon cancer cells [ 27 ]. Interestingly, P21, a direct downstream protein regulated by P53, was effectively induced by TCEE treatment on the P53-deficient Hep3B cells.…”
Section: Discussionsupporting
confidence: 59%
“…In both Hep3B and HepJ5 cells, TCEE treatment induced the expression of cell cycle inhibitors, P21 and P27. Similar P21 induction by TCEE was observed in human melanoma and osteosarcoma cells [ 16 ], whereas the P27 induction by TCEE was observed in human colon cancer cells [ 27 ]. Interestingly, P21, a direct downstream protein regulated by P53, was effectively induced by TCEE treatment on the P53-deficient Hep3B cells.…”
Section: Discussionsupporting
confidence: 59%
“…These results allowed us to determine some preliminary structure-activity relationships among the different small carbocyclic and heterocyclic systems substituted in the acyl region. Thus, acylselenourea derivatives with benzodioxyl, a well-known chemotherapeutic heterocycle [55,[67][68][69] (10a-c and 10e), seemed to be more active than all of the other synthesized acylselenourea derivatives. Nevertheless, among the different substituents (H, Me, OCH 3 , CF 3 , and Cl) on the aniline ring, these groups seemed not to be important for the inhibition of cell viability.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…These findings showed that AC can be used as adjuvant antitumor agent for T 29 human colon cancer cell xenograft tumors [86]. Tu et al, [85] demonstrated that SY-1 isolated from dried fruiting bodies of AC inhibited the growth of COLO-25 cell xenograft tumors through the inhibition of p53-mediated cell cycle regulatory genes. SY-1 inhibited the cell growth in both COLON-205 and HepG2 cells that exhibits wild type p53 and cancer cell lines that have mutant p53 in dose and time-dependent manner.…”
Section: Dna Damage and Apoptosis Biomarkers Activationmentioning
confidence: 94%
“…In numerous studies it has been shown that AC demonstrates cell cycle inhibition and apoptotic cell death that are both contributing to its antitumor effect. Tu and his team [85] demonstrated that a purified compound from AC (4,7dimetohoxy-5-methyl-1,3-benzodioxole; SY-1) can be used as apoptosis inducer in COLO-25 colon cancer cells. SY-1 also induced cell cycle arrest in G0/G1 phase through the activation of p53-mediated cyclin-dependent kinase (CDK) inhibitor expression.…”
Section: Dna Damage and Apoptosis Biomarkers Activationmentioning
confidence: 99%